2006
DOI: 10.3892/or.16.3.555
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of perinecrotic tumor cell nuclei in glioblastomas shows a significant relationship with survival time

Abstract: A deeper knowledge about histopathological criteria with a significant impact on the prognosis of patients with glioblastomas is worthwhile, since these patients may show a considerable difference in the time of survival. Investigation of the morphology of perinecrotic tumor cell nuclei is a promising approach, because the expression of specific molecules in these cells has been associated with a more aggressive behaviour of the tumors. In our series of patients with documented clinical course, 11 patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Histomorphometry of tumour cell nuclei could also be a promising approach for estimation of the prognosis for individual patients. It was shown that the nuclei had a tendency toward a more circular shape in short survivors [22, 23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histomorphometry of tumour cell nuclei could also be a promising approach for estimation of the prognosis for individual patients. It was shown that the nuclei had a tendency toward a more circular shape in short survivors [22, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…For the analysis of the nuclear shape in the control and drug-treated cells, the roundness factor was used [22, 23] with value 1 for a circle and smaller values for increasing irregularities of nuclear shape. For visualisation of the nucleus, the cells were stained with Hoechst 33342 at a final concentration of 80 μg/ml for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…A limited number of investigations paid attention to the possible prognostic value of cytological and histological features. Nafe et al reported that the main cytological difference between STS and LTS is the increase of the nuclear density in necrotic areas of the lesions, resulting in a reduction in the internuclear distance in STS patients [40]. Finally the role of Ki67, the number of mitosis and extent of necrosis as a negative prognostic value is uncertain [18,40].…”
Section: Discussionmentioning
confidence: 99%
“…One approach to assigning cystosolic areas to individual cells it to start with the segmentation of cell nuclei. Furthermore, the morphology of nuclei is also commonly used as an indicator for various cellular states, such as apoptosis or necrosis [1], [2] and can represent important phenotypic features in classifying the effect of toxins or evaluating the longevity of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been suggested that mitochondria in neurons from PD animal models undergo significant changes in mitochondrial membrane potential [6]. In order to study potential tipping points between healthy and diseased cellular states, it is crucial to study single cells and to analyze single cell variation over time in order to 1 Luxembourg Centre for Systems Biomedicine (LCSB), University of Luxembourg 2 National Center for Microscopy & Imaging Research, University of California, San Diego catch rare events in mitochondrial membrane potential [7], [8]. HeLa cells have a tendency to grow in monolayers due to the nature of 2D cell culture conditions.…”
Section: Introductionmentioning
confidence: 99%